Forecasting the oil price using house prices - Rainer Schulz; Martin Wersing (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2015)
We show that house prices from Aberdeen in the UK improve in- and out-of-sample oil price forecasts. The improvements are of a similar magnitude to those attained using macroeconomic indicators. We explain these forecast improvements with the dominant role of the oil industry in Aberdeen. House prices aggregate the dispersed knowledge of the future oil price that exists in the city. We obtain similar empirical evidence for Houston, another city dominated by the oil industry. Consistent with our explanation, we find that house prices from economically more diversified areas in the UK and the US do not improve oil price forecasts.
Keywords: C53; E32; Q47; R31; 330; oil price forecasting; house prices; knowledge spillover